How family physicians in Singapore recognise complexity during consultations: a qualitative study - Jing Sheng Quek; Eng Sing Lee; Lian Leng Low; Sabrina Kay Wye Wong (BMC Primary Care, 2024)
Abstract Background The prevalence of persons with complex needs in Singapore is rising. Poor understanding of what constitutes complexity impedes the identification of care gaps and development of interventions to improve care for these individuals. We aim to identify the characteristics contributing to complexity in primary care, from the Family Physicians’ (FP) perspectives. Methods Focus group discussions (FGDs) were conducted from January to September 2021 with experienced FPs across 14 study sites, employing a qualitative descriptive approach based on a complexity framework. Data were coded independently and categorised using thematic analysis by two independent investigators. Results Five FGDs were conducted with 18 FPs aged 32 to 57 years old working in different primary care settings, with a mean of 13.5 years of primary care experience. Participants emphasised the need for a unified definition of complexity. Complexity is characterised by the presence of issues spanning across two or more domains (medical, psychological, social or behavioural) that adversely impact medical care and outcomes. Persons with complex needs contrast with persons with medically difficult issues. Medical domain issues include the number of active medical problems, poor chronic disease control, treatment interactions, ill-defined symptoms, management of end-of-life conditions and functional impairment. Psychological domain issues include the presence of mental health conditions or cognitive impairment. Social domain issues include the lack of social support, competing social responsibilities and financial issues, while behavioural domain issues include a lack of trust in healthcare workers, fixed health beliefs and poor health literacy. Conclusion Recognising the medical, psychological, social and behavioural factors that contribute to complexity aids in discerning the diverse needs of individuals with complex needs. This underscores the need for additional support in these pertinent areas.